2021
DOI: 10.3390/su13168897
|View full text |Cite
|
Sign up to set email alerts
|

The Informal Seed Business: Focus on Yellow Bean in Tanzania

Abstract: This article explores the informal seed business, focusing on the yellow bean in Tanzania. The yellow bean is a major bean type traded, yet little is known about the seed supply that fuels it. The survey research in 2019 encompassed larger grain traders, informal seed traders, and retailers, covered major production, distribution and sale hubs, and was complemented by GIS mapping of seed and grain flows and DNA fingerprinting of yellow bean samples. Results showed that traders buy and sell grain and informal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Yellow beans are also important in African countries including Angola, Tanzania, and Kenya (Buruchara et al 2011). In fact, yellow beans fetch higher prices than other seed types in Zambia (Sichilima et al 2016), are some of the most traded types in Tanzania (Sperling et al, 2021), and they are the most preferred type in Uganda (Kilimo Trust 2012). A few of the most important yellow market classes include Manteca, Canary, and Mayocoba in Latin America, and Njano in Tanzania (Sones 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yellow beans are also important in African countries including Angola, Tanzania, and Kenya (Buruchara et al 2011). In fact, yellow beans fetch higher prices than other seed types in Zambia (Sichilima et al 2016), are some of the most traded types in Tanzania (Sperling et al, 2021), and they are the most preferred type in Uganda (Kilimo Trust 2012). A few of the most important yellow market classes include Manteca, Canary, and Mayocoba in Latin America, and Njano in Tanzania (Sones 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Pan-Africa Bean Research Alliance (PABRA) and the Alliance of Bioversity International and International Centre for Tropical Agriculture (ABC) surveyed yellow bean trading and market size in Eastern and Southern Africa regions including Tanzania, Burundi, DRC, Kenya, Rwanda, Uganda, and Zambia. The study revealed the growing popularity of yellow beans in the region, a vibrant informal seed system adept at incorporating new varieties, and that consumer preferences for yellow beans are especially associated with palatability and fast cooking times (Birachi et al, 2020;Sperling et al, 2021). Green-yellow shaded beans are referred to as Njano Kijani and Kijivu in Tanzania (Dr. Susan Nchimbi-Msolla, Sokoine University of Agriculture, Tanzania, personal communication), and Njano is a preferred type for home consumption in Tanzania (Sones 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the terms themselves are imprecise and can reinforce misconceptions. For instance, the term “informal” can misleadingly imply that such seed systems are not rule-governed, while “local” suggests that seed only circulates at limited geographic scales, while there is ample evidence to the contrary ( 20 23 ).…”
Section: Seed Systems: Theory and Practicementioning
confidence: 99%
“…This is not limited to local varieties. According to a recent study on yellow bean seed trade in Tanzania, 60% of the seeds acquired by farmers were improved varieties bought from local traders, two of which had only been released 1 to 3 y before, demonstrating rapid dissemination through trade networks ( 23 ).…”
Section: Seed Disseminationmentioning
confidence: 99%
“…East Africa is among the global leaders in common bean production, where Tanzania ranks rst in Africa and seventh worldwide (FAOSTAT, 2021). Over 75 per cent of the rural households in Tanzania depend on beans for their daily subsistence (Katungi et al, 2019;Sperling et al, 2021). Despite common bean's potential as a food crop, for nutrition and as source of income, on-farm productivity in Tanzania remains low, at 1.4 t/ha (FAOSTAT 2021) compared with onstation productivity of 2-2.5 t/ha (Kiriba et al, 2019;Binagwa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%